2009
DOI: 10.1007/s12311-009-0141-5
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar Lingula Size and Experiential Risk Factors Associated with High Levels of Alcohol and Drug Use in Young Adults

Abstract: Previous studies have reported cerebellar abnormalities or static ataxia associated with risk for chronic use of alcohol and drugs. Adverse childhood experience (ACE) is another strong risk factor for later substance abuse. We therefore, sought to ascertain the relationship between morphological phenotypes of the lingula (Lobule I) of the anterior cerebellar vermis (ACV), and exposure to emotional (EM) versus physical (PM) maltreatment,on the degree of ongoing alcohol or drug use. The study design consisted of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
22
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 78 publications
(82 reference statements)
5
22
0
1
Order By: Relevance
“…As in our previous studies of subjects exposed to VA (5, 6, 12), self-report ratings were obtained using Kellner's Symptom Questionnaire (SQ; (13)), the Dissociative Experience Scale (DES; (14)) and the Limbic System Checklist-33 (LSCL-33; (15)). The SQ provides four symptom scales (depression, anxiety, anger-hostility, somatic complaints).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As in our previous studies of subjects exposed to VA (5, 6, 12), self-report ratings were obtained using Kellner's Symptom Questionnaire (SQ; (13)), the Dissociative Experience Scale (DES; (14)) and the Limbic System Checklist-33 (LSCL-33; (15)). The SQ provides four symptom scales (depression, anxiety, anger-hostility, somatic complaints).…”
Section: Methodsmentioning
confidence: 99%
“…This has been shown to be true for early exposure to childhood sexual abuse (CSA), physical abuse (PA), witnessing domestic violence (WDV) and composite scores reflecting exposure to multiple forms of trauma (4). Previously, we reported that parental verbal abuse (VA) is an important, but often overlooked, form of childhood adversity that was more strongly associated with symptom ratings such as depression and anger-hostility than parental PA (5, 6). …”
Section: Introductionmentioning
confidence: 99%
“…In line with this argument, specific attention may be given to the role of the cerebellum. The cerebellum is a brain region that has consistently demonstrated volumetric (42)(43)(44)(45)(46)(47) and functional abnormalities (48)(49)(50)(51) in individuals with heavy alcohol consumption. To date, there have been few investigations of cerebellar function in young adults in relation to impulsive behaviour and substance use.…”
Section: Discussionmentioning
confidence: 99%
“…In this issue, a careful examination of the morphology of the anterior cerebellar vermis by Anderson et al [6] reveals that a high-level consumption of hard liquor in young adults who have not previously showed alcohol dependence is associated with a marked thickening of lobule I (lingula). Increased lingula thickness is found in case of greater consumption of drugs and hard liquor, particularly in physically maltreated subjects who have consumed more alcohol and have used drugs more frequently than controls.…”
mentioning
confidence: 99%
“…Genetic susceptibility interacts with experience to determine outcome [6]. Exposure to childhood adversity is now considered as a major experiential risk factor.…”
mentioning
confidence: 99%